2012
DOI: 10.3109/03630269.2012.742911
|View full text |Cite
|
Sign up to set email alerts
|

Hb Iberia [α104(G11)Cys → Arg,TGC>CGC (α2) (HBA2:c.313T>C)], a Newα-Thalassemic Hemoglobin Variant Found in the Iberian Peninsula: Report of Six Cases

Abstract: We report a new structural defect of the α2-globin chain presenting with moderate microcytic hypochromic anemia, in six individuals from three unrelated families, living in Portugal and Spain. α-Globin gene deletions were ruled out by gap-polymerase chain reaction (gap-PCR) and multiplex ligation-dependent probe amplification (MLPA). Direct sequencing of the α2-globin gene revealed a substitution of codon 104 [α104(G11)Cys→Arg, TGC>CGC (α2) (HBA2:c.313T>C)]. This new variant, not detectable by high performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Hemoglobin polymorphisms reveal severe protein instability in Hb from people with Cys104 mutations in their HbA1 or HbA2 genes. Reported mutations include HbA2 αCys104Arg [Hb Iberia, ( Bento et al, 2012 )], HbA2 αCys104Tyr [Hb Sallanches, ( Morle et al, 1995 )], HbA1 αCys104Ser [Hb Oegstgeest, ( Harteveld et al, 2005 )] and HbA1 αCys104Trp (alpha codon 10 TGC-TGG). In these cases, the protein is too unstable to be detectable in heterozygotes or associated with thalassemia in homozygotes.…”
Section: Discussionmentioning
confidence: 99%
“…Hemoglobin polymorphisms reveal severe protein instability in Hb from people with Cys104 mutations in their HbA1 or HbA2 genes. Reported mutations include HbA2 αCys104Arg [Hb Iberia, ( Bento et al, 2012 )], HbA2 αCys104Tyr [Hb Sallanches, ( Morle et al, 1995 )], HbA1 αCys104Ser [Hb Oegstgeest, ( Harteveld et al, 2005 )] and HbA1 αCys104Trp (alpha codon 10 TGC-TGG). In these cases, the protein is too unstable to be detectable in heterozygotes or associated with thalassemia in homozygotes.…”
Section: Discussionmentioning
confidence: 99%
“…Although α-thal is commonly associated with the -α 3.7 and -α 4.2 deletions (6), two novel α-thalassemic Hb variants have already been described in the Portuguese population, Hb Evora (HBA2: c.106T>C; p.Ser36Pro) (7) and Hb Iberia (HBA2: c.313T>C; p.Cys105Arg) (8). Hb Plasencia can easily be 184 E. Cunha et al identified by restriction enzyme digestion.…”
mentioning
confidence: 99%